2020
DOI: 10.3390/healthcare8040416
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitude and Practices of the Caregivers about Oral Health Care, at Centers for Intellectually Disabled, in Southern Region of Saudi Arabia

Abstract: Oral health is perhaps the most neglected aspect of healthcare for persons living in rehabilitation centers, compared to the general population. The caregivers play a vital role in administering daily oral care to residents in rehabilitation centers: The aim of the present questionnaire-based study was to evaluate the caregivers’ knowledge, attitude and practices towards oral healthcare at centers for the intellectually disabled in the Southern region of Saudi Arabia (SA). The present study was designed as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 23 publications
3
23
1
2
Order By: Relevance
“…In the same vein, a slightly higher percentage was indicated by the study of (70) conducted in Italy, which revealed that approximately three-quarters affirmed not knowing the disease, and with a lower percentage, approximately one-quarter aware of the diseases. This contradicts the findings of a study conducted in Saudi Arabia by (71) which found that one-quarter of caregivers had a poor level of knowledge, three-fifths had a reasonable level of knowledge, and one-fifth had a strong level of knowledge.…”
Section: Discussioncontrasting
confidence: 92%
“…In the same vein, a slightly higher percentage was indicated by the study of (70) conducted in Italy, which revealed that approximately three-quarters affirmed not knowing the disease, and with a lower percentage, approximately one-quarter aware of the diseases. This contradicts the findings of a study conducted in Saudi Arabia by (71) which found that one-quarter of caregivers had a poor level of knowledge, three-fifths had a reasonable level of knowledge, and one-fifth had a strong level of knowledge.…”
Section: Discussioncontrasting
confidence: 92%
“…This can be done by providing assistance to students so that slowly other students will follow the behavior of maintaining dental health fully and consciously, because by seeing, listening and interacting, students will be able to respond to what they get and manifest it in practice or action (Apesteguia, Huck, Oechssler, Weidenholzer, & Weidenholzer, 2018). Research by Abullais, et al, (2020) and Ahamed et al, (2015) said that adherence was also influenced by gender where adherence to dental health maintenance of female participants was better than that of male participants.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan yang tinggi akan menujukkan perilaku yang positif dalam melakukan perawatan gigi, dan sebaliknya apabila pengetahuan dari suatu individu kurang baik, maka akan tercermin dari perilakunya dalam menjaga kesehatan gigi [21]. Maka, mengembangkan strategi promosi kesehatan gigi dan mulut yang efektif dalam suatu komunitasi di mana pun berada harus didasarkan pada pemahaman tentang kebutuhan khusus suatu komunitasi tersebut [22].…”
Section: Penelitianunclassified